Efeitos da compensação de gestores por meio de opções de ação sobre as decisões de pagamento de dividendos e de recompra de ações das firmas brasileiras - Felipe Rodrigues Cruz (2018)
The context of modern corporations is marked by the division of ownership and managerial control, which brings a series of interest conflicts between shareholders and managers, because they have different utility functions. The necessity to align the conflicting interests of managers and shareholders is the focus of the literature that studies the Agency Theory. Recently, it has been indicated in the finance literature that the agency relations can assist in the explanation of decisions related to the corporate payout. The focus of these studies is the analysis of the impact of specific management compensation plans on the decisions related to the corporate payout, highlighting the analysis of management stock options. A review of previous theoretical and empirical studies on Agency Theory, Corporate Payout and the relationship between these two themes was carried out in the present study. In an attempt to make up for the lack of studies on the theme in the Brazilian scenario, an analysis was carried out in the present research to assess how the presence of stock options in the managers payment scheme impacted the decisions on dividend payments and stock repurchases in companies traded on BM&FBovespa. It was possible to identify that the managers exercisable options negatively impacted the dividend payments, since managers avoid the reduction in the price of shares on the ex-dividend date tied to dividend payments, which results in the reduction of the value of their options. In addition, it was identified that firms that remunerate their managers through options are more likely to repurchase shares, because it is not expected that this form of earnings distribution will result in a negative impact on the value of their options. The evidence lead to the conclusion that these managers replace the payment of dividends by shares repurchases, because the options had a positive influence on the percentage of the repurchases on the total payment and did not have a significant impact on the total payout. It should be stressed that the consideration of the different hierarchical levels of managers compensated by options was relevant to the analysis of the results. Finally, we investigate whether managers remunerated by options that present pressure to raise the stock market price utilized repurchase announcements as a way of influencing market decisions, seeking to send false signals of stock undervaluation to the market through the announcements of repurchase, without the intention to execute the promised repurchases. The management of accruals was used to identify firms that were under pressure to send positive signals. It was not possible to associate management options to false signaling attempts, however, it was identified that firms which were under pressure to send positive signals to the market were less prone to execute their repurchase announcements, indicating that these announcements could be attempts to manipulate the stock market value.